2021
DOI: 10.1108/lht-07-2020-0165
|View full text |Cite
|
Sign up to set email alerts
|

Toward the e-loyalty of digital library users: investigating the role of e-service quality and e-trust in digital economy

Abstract: PurposeThis study aims to investigate the role of e-service quality and e-trust for achieving e-loyalty among digital library users in the digital economy. The current study examined the mediation effect of e-trust in the connection between e-service quality and e-loyalty.Design/methodology/approachCross-sectional design was applied for the purpose of data collection and empirical findings of the study. Survey method was used for the purpose of data collection from 783 online digital libraries users.FindingsRe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 83 publications
4
23
0
2
Order By: Relevance
“…Based on the results of data analysis, the p-value value is 0.000 < 0.050 so it can be concluded that e-Service Quality has a positive and significant effect on e-Loyalty, this result is in line with the findings of Al Dmour et al (2019);Al-Khayyal et al (2020); Anser et al (2021); Azemi et al (2015) that e-Service Quality has a positive and significant effect on e-Loyalty and According to Salehnia et al (2014); Shankar et al (2019); Suariedewi et al (2020); Sumithra et al (2019);Tri et al (2018) that e-Service Quality has a positive and significant effect on e-Loyalty. Increasing the e-Service Quality variable will encourage a positive and significant increase in the e-Loyalty variable H3: e-Trust and its effect on e-Service Quality Based on the results of data analysis, the p-value value is 0.000 < 0.050 so it can be concluded that e-Trust has a positive and significant effect on e-Service Quality, this result is in line with the findings of Ahmad et al (2017) 2017) that e-Trust has a positive and significant effect on e-Service Quality.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Based on the results of data analysis, the p-value value is 0.000 < 0.050 so it can be concluded that e-Service Quality has a positive and significant effect on e-Loyalty, this result is in line with the findings of Al Dmour et al (2019);Al-Khayyal et al (2020); Anser et al (2021); Azemi et al (2015) that e-Service Quality has a positive and significant effect on e-Loyalty and According to Salehnia et al (2014); Shankar et al (2019); Suariedewi et al (2020); Sumithra et al (2019);Tri et al (2018) that e-Service Quality has a positive and significant effect on e-Loyalty. Increasing the e-Service Quality variable will encourage a positive and significant increase in the e-Loyalty variable H3: e-Trust and its effect on e-Service Quality Based on the results of data analysis, the p-value value is 0.000 < 0.050 so it can be concluded that e-Trust has a positive and significant effect on e-Service Quality, this result is in line with the findings of Ahmad et al (2017) 2017) that e-Trust has a positive and significant effect on e-Service Quality.…”
Section: Resultssupporting
confidence: 83%
“…In economic transactions there are interactions between sellers and buyers to strengthen long-term relationships between sellers and buyers as well as in e-banking transactions, the bank tries to build and maintain long-term relationships or bonds with its customers. According to Al-Khayyal et al (2020); Anser et al (2021); Azemi et al (2015) In e-banking, the existence of physical separation between banks and their customers and the absence of physical interaction between consumers and bank employees in e-banking causes a unique situation, so that trust from consumers is the most important thing for banks. The advantage of providing e-banking services for banks is that e-banking can be an inexpensive solution for infrastructure development compared to opening an ATM outlet.…”
Section: Introductionmentioning
confidence: 99%
“…Loyalty has been stressed by several authors as being one of the most important factors which determine the success of a company Kartika et al, 2020;Latif et al, 2021;Anser et al, 2021;Guan et al, 2021). In terms of these findings, it is important for a company to be able to instill loyalty in its consumers' minds in a consistent manner, in order to prevent them from buying products from competitors.…”
Section: Introductionmentioning
confidence: 99%
“…These items were adapted from the work of Kim et al (2009). The items generated an alpha value of "(1) I believe that Internet shopping is a secure activity., (2) Ecommerce sites are trustworthy, (3) e-commerce webs give the impression that they will keep commitments., ( 4) I have high level trust level in e-commerce activities and webs" [22]. E-trust mediates the relationship between e-Marketing orientation (EMO) and strategic business performance (SBP) [23] the result showed that e-trust had a positive and significant relationship with e-satisfaction and e-loyalty and e-trust mediated the relationship between website quality and e-loyalty [24] Also, this result indicates that e-trust is a mediator between esatisfaction and e-loyalty.…”
Section: Discussionmentioning
confidence: 99%